A influência do nióbio na resistência à fadiga de liga de ferro fundido nodular austemperado - Cunha, Filipe Fernando da (My University, 2025)
This master's thesis investigates the influence of niobium addition on the mechanical properties and fatigue strength of austempered ductile iron (ADI), with the aim of evaluating its potential as a partial substitute for molybdenum and exploring industrial applications. Three alloys were produced with niobium contents of 0 %, 0.23 %, and 0.29 %, and subjected to austempering heat treatment. The samples were characterized in terms of chemical composition, microstructure, mechanical properties (tensile strength, impact strength, hardness), and rotating bending fatigue strength. The addition of niobium reduced nodularity, and nodule density and promoted the formation of niobium carbide (NbC), confirmed by SEM and EDS analyses. A significant increase in yield strength was observed with 0.23 % Nb, along with a decrease in elongation at 0.29 % Nb. Toughness showed a non-monotonic trend, improving at 0.23 % and declining at 0.29 %, while hardness increased with niobium content, although with greater dispersion in the alloy with the highest concentration. In fatigue tests, the alloy without niobium showed high data dispersion and a low correlation coefficient (R² = 0.3), whereas the niobium containing alloys exhibited greater uniformity and predictability (R² = 0.80 and 0.76). However, the endurance limit was reduced by 0.23 % Nb and was partially recovered with 0.29 % Nb. The results indicate that niobium addition contributes to increased mechanical strength and reduced variability in fatigue behavior for finite life, with 0.23 % Nb being the most promising content for applications requiring higher reliability. The results suggest that niobium, as an alloying element, can enhance the mechanical properties of austempered ductile iron. Nevertheless, the agglomeration of primary NbC carbides tends to impair toughness, ductility, and endurance limit. [resumo fornecido pelo autor]
Esta dissertação investigou a influência da adição de nióbio nas propriedades mecânicas e na resistência à fadiga de um ferro fundido nodular austemperado (ADI -Austempered Ductile Iron), com o objetivo de avaliar seu potencial como substituto parcial do molibdênio e explorar aplicações industriais. Foram produzidas três ligas com teores de nióbio de 0 %, 0,23 % e 0,29 %, submetidas ao tratamento térmico de austêmpera. As amostras foram caracterizadas quanto à composição química, microestrutura, propriedades mecânicas (tração, impacto, dureza) e resistência à fadiga por flexão rotativa. A adição de nióbio reduziu a nodularização e a densidade de nódulos, além de promover a formação de carbonetos de nióbio (NbC), confirmados por MEV e EDS. Observou-se aumento significativo no limite de escoamento com 0,23 % de Nb e uma diminuição do alongamento com 0,29 % de Nb. A tenacidade apresentou comportamento não crescente, com melhora para 0,23 % e queda para 0,29 %, enquanto a dureza aumentou com o teor de Nb, porém com maior dispersão na liga de maior concentração. Nos ensaios de fadiga, a liga sem Nb apresentou alta dispersão e baixo coeficiente de correlação (R² = 0,3), ao passo que as ligas com nióbio mostraram maior uniformidade e previsibilidade dos dados (R² = 0,80 e 0,76). No entanto, o limite de fadiga para vida infinita foi reduzido para 0,23 % de Nb e parcialmente recuperada com 0,29 % de Nb. Os resultados indicam que a adição de nióbio contribui para o aumento da resistência mecânica e para a diminuição da variabilidade no comportamento da fadiga para vida finita, sendo o teor de 0,23 % o mais promissor para aplicações que demandam melhor confiabilidade. Os resultados indicam que a adição de nióbio, como elemento de liga, pode contribuir para a melhoria de propriedades mecânicas do ferro fundido nodular austemperado. Entretanto, a aglomeração de carbonetos primários de NbC tende a prejudicar a tenacidade, ductilidade e resistência à fadiga. [resumo fornecido pelo autor]
Keywords: Metais - Fadiga; Ferro fundido - Propriedades mecânicas; Nióbio; Metals - Fatigue; Cast Iron - Mechanical properties; Niobium